2019
DOI: 10.1001/jama.2019.7505
|View full text |Cite|
|
Sign up to set email alerts
|

Effect of Intraoperative High Positive End-Expiratory Pressure (PEEP) With Recruitment Maneuvers vs Low PEEP on Postoperative Pulmonary Complications in Obese Patients

Abstract: IMPORTANCE An intraoperative higher level of positive end-expiratory positive pressure (PEEP) with alveolar recruitment maneuvers improves respiratory function in obese patients undergoing surgery, but the effect on clinical outcomes is uncertain. OBJECTIVE To determine whether a higher level of PEEP with alveolar recruitment maneuvers decreases postoperative pulmonary complications in obese patients undergoing surgery compared with a lower level of PEEP. DESIGN, SETTING, AND PARTICIPANTS Randomized clinical t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
158
4
2

Year Published

2019
2019
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 251 publications
(188 citation statements)
references
References 32 publications
5
158
4
2
Order By: Relevance
“…There was no significant difference in preoperative BMI or STOP-Bang scores of obese patients between the two groups, which suggests that the risk of suffering respiratory depression in both groups was similar. With reference to previous studies, 19,26 oxygen desaturation in our study was defined as SpO 2 <92% for ≥10 sec, and apnea was defined as an absence of respiratory effort ≥10 sec. We defined hypoxemia for SpO2<92% for ≥10 s to exclude the interference of the plethysmographic pulse waveform.…”
Section: Discussionmentioning
confidence: 99%
“…There was no significant difference in preoperative BMI or STOP-Bang scores of obese patients between the two groups, which suggests that the risk of suffering respiratory depression in both groups was similar. With reference to previous studies, 19,26 oxygen desaturation in our study was defined as SpO 2 <92% for ≥10 sec, and apnea was defined as an absence of respiratory effort ≥10 sec. We defined hypoxemia for SpO2<92% for ≥10 s to exclude the interference of the plethysmographic pulse waveform.…”
Section: Discussionmentioning
confidence: 99%
“…The PEEP levels tested in the present study (2 and 6 cmH 2 O) represented a two-fold increase compared with humans (4 and 12 cmH 2 O), due to differences in transpulmonary pressures between humans and rats (Caironi et al, 2011). These PEEP levels were previously tested in clinical studies (Nestler et al, 2017;Pereira et al, 2018;Bluth et al, 2019).…”
Section: Discussionmentioning
confidence: 61%
“…A multicenter, international randomized controlled trial (PROBESE) compared the effects of two different levels of intraoperative PEEP (4 cmH 2 O versus 12 cmH 2 O) during protective low-V T ventilation in obese patients and observed no differences in PPCs (Bluth et al, 2019). Taking into account species differences, the PEEP levels used in our study and in PROBESE are comparable, but comparison between these two studies is unwarranted, since laparoscopy and recruitment maneuvers were performed in most patients.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…In another study, the PROVHILO trial (2014) demonstrated that a strategy consisting of a high level of PEEP combined with RM during open abdominal surgery does not protect against PPC; the authors conclude that the perioperative protective ventilation strategy should include low V T and low PEEP without RM [88]. The recent multicenter PROBESE trial (2019) also demonstrated that setting a high PEEP of 12 cmH 2 O and using RM in obese patients (body mass index > 35 kg/m 2 ) is not associated with any reduction of PPC compared to a low level of PEEP (4 cmH 2 O) [89]. The rationale for higher intraoperative PEEP and RM in thoracic surgery with one-lung ventilation is being explored in the ongoing PROTHOR trial (NCT02963025) [90].…”
Section: Protective Ventilation During Perioperative Periodmentioning
confidence: 99%